2013
DOI: 10.1145/2461912.2461986
|View full text |Cite
|
Sign up to set email alerts
|

Robust fairing via conformal curvature flow

Abstract: We present a formulation of Willmore flow for triangulated surfaces that permits extraordinarily large time steps and naturally preserves the quality of the input mesh. The main insight is that Willmore flow becomes remarkably stable when expressed in curvature space -we develop the precise conditions under which curvature is allowed to evolve. The practical outcome is a highly efficient algorithm that naturally preserves texture and does not require remeshing during the flow. We apply this algorithm to surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
113
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(114 citation statements)
references
References 25 publications
1
113
0
Order By: Relevance
“…However, we found that self‐intersections are often removed by cMCF early on, even for high genus shapes (see Figure 13). This is in contrast to the conformal Willmore flow [CPS13]. Our experiments show that this method removes all intersections at a much later state (see Figure 14).…”
Section: Experiments and Resultsmentioning
confidence: 76%
“…However, we found that self‐intersections are often removed by cMCF early on, even for high genus shapes (see Figure 13). This is in contrast to the conformal Willmore flow [CPS13]. Our experiments show that this method removes all intersections at a much later state (see Figure 14).…”
Section: Experiments and Resultsmentioning
confidence: 76%
“…For domains with boundary Bohle & Pinkall [BP13] showed that prescribing binormal boundary conditions preserves the self‐adjointness and ellipticity of the extrinsic Dirac operator (see [CPS13, Section 6.3] for a discretization); a similar argument may be possible for the relative Dirac operator. However, the shape of the boundary can cause trouble in spectral geometry processing particularly in the case of partial matching of surface patches [RCB∗17].…”
Section: Boundary Conditionsmentioning
confidence: 99%
“…Geometric surface flows have various applications within computer graphics [Eckstein et al 2007;Pan et al 2012;Crane et al 2013]. We consider multimaterial normal and mean curvature flows.…”
Section: Geometric Flowsmentioning
confidence: 99%